Students`Knowledge Level About Small Ball Games (Badminton) at Junior High School 2 Banjarbaru - Nanda Wahyu Hermawan; Mita Erliana; Abd.Hamid (Universitas Negeri Semarang, 2025)
The purpose of this study is to find out the level of knowledge of Junior High School 2 Banjarbaru students about the basic rules and techniques of the game of badminton. This research is included in Quantitative Descriptive research. The researcher used the Knowledge Population test method in the study of all students of Junior High School 2 Banjarbaru totaling 950 students, and the sample amounted to 200 students The researcher used the Porvosive Sampling Technique. The results of the students’ knowledge level about the game of small ball (badminton) at Junior High School 2 Banjarbaru, the very High category amounted to 18 students with a percentage of 9%, the High category amounted to 59 students with a percentage of 29.5%, the medium category amounted to 77 students with a percentage of 38.5%, the low category amounted to 34 students with a percentage of 17%, and the very low category amounted to 12 students with a percentage of 6%. The conclusion of the research results these findings indicate that although badminton has been taught as part of the physical education curriculum, there are still obstacles in mastering basic techniques such as serving, forehand, backhand, and footwork.